Expanding Context to Redefine Theories: Africa in Management Research - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2015)
As a scholarly field matures, theories emerge that guide paradigms and shape consensus in academic discourse. Management theories reflect a shared consensus on how individual behaviors or organizational actions result in a certain set of outcomes and under specific conditions. Clearly, theory is paramount to guiding whether models of potential relationships bear out and how and why we would expect a relationship or specific outcome. Yet much of this theory is derived from cumulative empirical evidence from a ‘context’ that has remained a silent partner in our quest for a theoretical contribution. A growing number of papers emphasize the theoretical contribution as disembodied from the context in which the empirical evidence of a causal relationship was gleaned. As an applied field, the emphasis on theory with disregard to the context of management practice presents a challenge for progress both as a scholarly domain and for credibility in what we teach and how we consult, or how we effect positive social change. This guest editorial joins a chorus of recent editorials in this journal (e.g., Tsui, 2013) and elsewhere (e.g., George, 2014) that suggest we rethink management scholarship, rejuvenate our ideas for research, and embed a nugget of practice in scholarly discourse.